Classification Of Network Load Traffic By taking advantage of Software Defined Network (Latakia University Journal -Engineering Sciences Series, 2024)
The current networks are experiencing exponential growth in network loads due to the rapid emergence of numerous network applications. As a result, networks have transitioned into the era of massive data centers and evolving patterns of network loads. This necessitates more efficient and effective network management techniques, particularly for monitoring network loads. This is where Software Defined Networks (SDN) come into play. SDN provides the advantage of centralized control by separating the control layer from the data layer. A significant challenge within the realm of SDN is the efficient classification of network load traffic to facilitate improved resource allocation and management. This paper categorizes network bearer traffic into two distinct categories: large traffic, often referred to as "elephant," and small traffic, known as "mice." Subsequently, we directed the large loads along a different route than the core network route. The results underscore the importance of the employed methodology in enhancing the load transfer process within the network.